The Effect of Early Skin to Skin Contact on Mother and Newborn Health: A systematic review - Ayşe YERLİKAYA; Selda İLDAN ÇALIM (Atatürk University, 2021)
Aim: The aim of this review is to investigate the effects of early skin to skin contact on maternal and infant health. Methods: The databases of Web of Science and Pubmed from Manisa Celal Bayar University e-library were searched using the search terms skin to skin contact, newborn health, mother health on November 20 to 25, 2018. Research articles which were published in English and were reached in full text in the last five years, A prospective, randomized controlled experimental study was conducted to investigate the effect of early skin to skin contact on maternal and neonatal health for preterm infants and low birth weight infants. Results: It was found that newborns begin to breastfeeding in less time, hypothermia' incidence decreased, the newborn adaptation to extrauterine life was easy. When the effect of skin to skin contact on the mother health was examined: it was found shortened third stage of labor, enhanced maternal-baby bonding, reduced the mother' pain perception, maternal postpartum depressive symptoms, maternal anxiety, and stress Conclusions: As a result of the studies with high level of evidence, it was found that early skin to skin contact positively affects maternal and neonatal health.